Effects and Mechanism of Auxin and Its Inhibitors on Root Growth and Mineral Nutrient Absorption in Citrus (Trifoliate Orange, Poncirus trifoliata) Seedlings via Its Synthesis and Transport Pathways - Yuwei Yang; Yidong Shi; Cuiling Tong; Dejian Zhang (Agronomy)
As an endogenous hormone, auxin plays a crucial role in regulating plants’ growth and development, and also in the responses to abiotic stresses. However, the effects and mechanism of auxin and its inhibitors on plant growth and mineral nutrient absorption in citrus have not been thoroughly studied. Therefore, we used trifoliate orange (citrus’s rootstock, Poncirus trifoliata) as the experimental material to supplement the research content in this area. The trifoliate orange seedlings were treated with exogenous auxin (indolebutyric acid, IBA) and auxin inhibitor (2-naphthoxyacetic acid, 2-NOA) in a sand culture system. The results showed that compared to the control, exogenous auxin (1.0 µmol L−1 IBA) significantly enhanced the taproot length, lateral root length, and lateral root number by 17.56%, 123.07%, and 88.89%, respectively, while also markedly elevating the levels of nitrogen (N), phosphorus (P), potassium (K), copper (Cu), and zinc (Zn) by 14.29%, 45.61%, 23.28%, 42.86%, and 59.80%, respectively. Again compared to the control, the auxin inhibitor (50.0 µmol L−1 2-NOA) dramatically reduced the taproot length, lateral root length, and lateral root number by 21.37%, 10.25%, and 43.33%, respectively, while also markedly decreasing the levels of N, magnesium (Mg), iron (Fe), Cu, and Zn by 7.94%, 10.42%, 24.65%, 39.25%, and 18.76%, respectively. Furthermore, IBA increased auxin accumulation in the root hair, stele, and epidermal tissues of citrus taproots, and promoted the up-regulation of auxin synthesis genes (TAR2, YUC3, YUC4, YUC6, YUC8) and transport genes (ABCB1, ABCB19, AUX1, LAX1, LAX2, PIN1, PIN3, PIN4). In contrast, 2-NOA decreased auxin levels in the root hair, stele, and epidermal tissues of citrus taproots, and was involved in the down-regulation of auxin synthesis genes (TAR2, YUC3, YUC4, YUC6) and transport genes (ABCB1, AUX1, LAX1, LAX2, LAX3, PIN3). Interestingly, 2-NOA dramatically elevated auxin level specifically in the root tip of citrus taproot. Therefore, 2-NOA disrupts auxin reflux from the root tip to root hair and epidermal tissues in citrus taproot through down-regulation of auxin transport genes, thereby creating localized (i.e., root hair zone and epidermal tissues) auxin deficiencies that compromise root system architecture and nutrient acquisition capacity. According to the results of this study, exogenous auxin analogs could regulate citrus growth and mineral nutrient absorption through the auxin synthesis and transport pathways.